Homogeneous and heterogeneous atmospheric ozonolysis of acrylonitrile on the mineral dust aerosols surface. Issue 6 (December 2021) - Wang, Naixian; Zheng, Peiming; Wang, Renqing; Wei, Bo; An, Zexiu; Li, Mingxue; Xie, Ju; Wang, Zeming; Wang, Hui; He, Maoxia
Abstract: Acrylonitrile (ACN) is a highly toxic substance that exists widely in the environment. It can pollute the environment and endanger human health. VOCs prone to nucleation and heterogeneous reaction on the mineral dust aerosols surface. Based on the DFT calculation, the ozonolysis processes of ACN in homogeneous reactions, heterogeneous reactions on Six Oy (OH)z clusters surface and heterogeneous reactions on (Al2 O3 )n clusters surface were studied in this paper. Ozone addition was the rate-determining step for ozonolysis of ACN with the rate constant of 2.03 × 10 −18 cm 3 molecule −1 s −1 at 298 K and 1 atm. Toxicity assessment showed that ozonolysis degradation effectively reduced the ecotoxicity of ACN. In this study, six kinds of non-metallic oxides Six Oy (OH)z clusters and thirteen kinds of metal oxides (Al2 O3 )n clusters were selected to simulate the adsorption behavior of ACN adsorbed on different mineral dust aerosols surface. ACN-Six Oy (OH)z cluster polymers formed hydrogen bond interactions, while ACN-(Al2 O3 )n cluster polymers mainly formed metallic bonds (Al-N), and they also had hydrogen bond interactions. The adsorption of Six Oy (OH)z clusters and (Al2 O3 )n clusters did not change the reaction mechanisms for ozonolysis of ACN, but affected the reaction rate constant to varying degrees. In addition, it was found that the adsorption modes of mineral dust aerosols surface had no correlation with the rate constants for ozonolysis of ACN. Graphical Abstract: ga1 Highlights: The processes of ACN reacting with O3 in homogeneous and heterogeneous were studied. Toxicity assessment showed that ozonolysis effectively reduced the ecotoxicity. ACN-Six Oy (OH)z formed hydrogen bonds, while ACN-(Al2 O3 )n mainly formed Al-N bonds. The adsorption didn't change reaction mechanisms but affected the rate constant. The adsorption manners had no correlation with the rate constants for ozonolysis of ACN.